Pemanfaatan Financial Technology Dalam Meningkatkan Akses Modal Bagi Pelaku Ekonomi Hijau dan Ekonomi Biru - Susanto, Marcell Willard; Sutarto, Sudarynianto Nurathaya; Rohman, Rizal Asy Ary; R.Pandin, Maria Yovita (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research was conducted to be able to determine the development of the rate of financial innovation in facilitating increased capital for green economy and blue economy actors as a means of contributing to providing sources of information on related topics and finding out more about economic sustainability in Indonesia by understanding the dynamics of the development of financial innovation, so that it can identifying the opportunities and challenges that exist in encouraging sustainable economic sector growth in the hope of providing a clearer picture of the importance of supporting the green economy and blue economy. The method we use is qualitative, which is used in this research process, obtained through an interview process with Green and Blue Economic Actors such as vegetable and fish sellers in the market, after which we explain and re-analyze the related concepts to obtain problem formulation and conclusions from conducting the analysis. the. The results obtained from this interview are that the use of Financial Technology has proven to be easier for economic actors, and accessing capital for business development can be done easily through financial innovation in the Financial Technology section, making it easier for green and blue economic actors.obtain the formula of problems and conclusions that exist from conducting such analysis